A new species of Suphisellus Crotch from Mexico (Coleoptera: Noteridae) - Arce-Pérez, Roberto; Baca, Stephen M. (Zootaxa, 2017)
Suphisellus epleri sp. nov. is described from Veracruz, Mexico. The new species is characterized by (1) size; (2) elytra brownish-red, moderately punctate, each with three light-yellow spots; and (3) aedeagus with median lobe curved with width nearly uniform along its length. In appearance, S. epleri is very similar to S. neglectus Young 1979 with which it is here compared based on specimens collected from Colombia and Venezuela. Suphisellus epleri is distinguished by having a slightly broader anterior extremity of prosternal process and a slender median lobe that is not distinctly expanded at apex, as in S. neglectus. The first record of S. neglectus in Venezuela is also reported. Descriptions, images and illustrations of diagnostic characters, and differential diagnosis of S. epleri are provided.